Management of Adolescent Midwifery Care for Ms. "M" with Moderate Anemia at Guppi Samata Gowa High School: Manajemen Asuhan Kebidanan Remaja pada Nn”M” dengan Anemia Sedang di SMA Guppi Samata Gowa - Yuliani Safitri,; Anieq Mumthiâ€™ah Al Kautzar,; Ferawati Taherong, (Jurnal Midwifery, 2023)
Introduction Anemia is a condition in which someone lacks enough healthy red blood cells in blood circulation to carry adequate oxygen to all body’s tissues. Anemia occurs since the hemoglobin (Hb) level in the blood is lower than the normal value in which the number level is mostly based on age and sex. In adolescent period, the normal hemoglobin level for female is around 12-15gr%. Method This case study used 7 stages of Varney to analysis. Result The findings of this case study indicated that the patient, 16 years old, experienced various issues such as being weak, tired, sleepy, dizzy and anxious. In addition, she also felt some headache. With the complaints, several measures were taken by health workers. The examination on the patient was conducted, and the patient was administered with both pharmacological and non-pharmacological drugs to reduce the pain. Moreover, the midwives also played an important role in providing health care to the patient, including herfamilies Conclusion This study concluded that the midwifery care management given to Ms. “M” with the case of anemia was considered to be good and well managed in which no particular problems occcurred during the curing process